2013
DOI: 10.1371/journal.pone.0073950
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects on DNA Methylation and Its Potential Relevance for Obesity in Mexican Americans

Abstract: Several studies have identified effects of genetic variation on DNA methylation patterns and associated heritability, with research primarily focused on Caucasian individuals. In this paper, we examine the evidence for genetic effects on DNA methylation in a Mexican American cohort, a population burdened by a high prevalence of obesity. Using an Illumina-based platform and following stringent quality control procedures, we assessed a total of 395 CpG sites in peripheral blood samples obtained from 183 Mexican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…This model is supported by our EMSA data demonstrating impaired SOX6 binding to a MEST promoter template with adjacent CpG methylation. Our findings therefore extend published observations that obesity significantly associates with decreased methylation levels at the MEST gene (Soubry et al, 2015), that MEST hypomethylation is linked to metabolic programming in offspring with a background in gestational diabetes (El Hajj et al, 2013), and that there is an inverse relationship between MEST CpG methylation levels and body composition measures, such as waist circumference and body mass index (Carless et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…This model is supported by our EMSA data demonstrating impaired SOX6 binding to a MEST promoter template with adjacent CpG methylation. Our findings therefore extend published observations that obesity significantly associates with decreased methylation levels at the MEST gene (Soubry et al, 2015), that MEST hypomethylation is linked to metabolic programming in offspring with a background in gestational diabetes (El Hajj et al, 2013), and that there is an inverse relationship between MEST CpG methylation levels and body composition measures, such as waist circumference and body mass index (Carless et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, information in cancer-free populations with metabolic diseases is much more limited, with the added issue of race and gender differences [21]. Emerging evidence suggests that gene-specific DNA methylation in blood cells may play an important role in obesity etiology [12,19,22,23,24,25,26]. Recently, epigenetic wide-association studies have demonstrated a strong association between body mass index (BMI) and DNA methylation in multiple loci [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty studies included breast cancer-free individuals. Of these, two included only women (13, 25), 16 included both men and women (24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), one was a meta-analysis of three cohorts (KORA, LOLIPOP, EPICOR) (41) and another a meta-analysis of two cohorts (FHS, LBC) (42). Three studies had mixed breast cancer patients and breast cancer-free Discovery sample column: *n not obese/n obese; # Data from meta-analysis are combined; ˚Mean between women's data and men's data; NW stands for normal weight, OW for overweight, OB for obese and V for visit.…”
Section: Resultsmentioning
confidence: 99%